Concurrent Radiation and Immunotherapy for Unresectable Hepatocellular Carcinoma With Extensive Portal Vein Tumor Thrombus - Nithya Krishnamurthy, BA; Daniel Cherry, MD; Carlos Rodriguez-Russo, MD; Michael Buckstein, MD (Advances in Radiation Oncology)
Purpose: While immunotherapy has been established as the standard of care for patients with Barcelona Clinic for Liver Cancer class C hepatocellular carcinoma (HCC), outcomes for patients with portal vein thrombus (PVT) remain poor. This study evaluates the benefit of radiation therapy (RT) in addition to immunotherapy for patients with advanced PVT. Methods and Materials: A retrospective chart screen was performed to identify patients with HCC with PVT treated with definitive RT with concurrent (defined as within 6 weeks) immunotherapy. Kaplan-Meier survival analysis was performed to assess progression-free survival (PFS) and overall survival (OS). Cox proportional hazard modeling was employed for each covariate using R software version 4.3.3. Results: Sixty-two patients met the inclusion criteria from 2016 to 2023. The median follow-up was 18.9 months. Most patients were male (85.8%), with a median age of 64, and 61% had Child-Turcotte-Pugh (CTP) A liver function. Treatments included stereotactic body RT (61%) or fractionated RT (39%) with immunotherapy (74% single-agent). Portal vein tumor thrombosis classifications were Vp3 (47%) and Vp4 (45%). Median overall PFS was 3.70 months, and OS was 7.7 months. Patients with CTP A had better outcomes (PFS 5.3 months, OS 10.2 months; PFS hazard ratio 2.13, OS hazard ratio 3.08, P < .05). There was no significant difference in PFS or OS for patients who received single-agent immunotherapy with radiation versus multiagent immunotherapy (atezolizumab-bevacizumab) with radiation. Multivariate analysis identified no other significant predictors. Conclusions: The addition of radiation to immunotherapy may improve outcomes for patients with advanced PVT with HCC who have inferior outcomes with immunotherapy alone. Particularly for patients with CTP A liver function who would be eligible for clinical trials, the addition of radiation may improve OS beyond reported outcomes. Prospective studies are needed to verify these results.